Penerapan Sistem Cook-Fresh Dalam Produksi Makanan di Instalasi Gizi Rumah Sakit Muhammadiyah Gresik - Amelia Putri Agustin; Niken Purwidiani; Ila Huda P Dewi; Aisyah Nurin Kamiliya (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the implementation of the cook-fresh system in food production at the Nutrition Installation of Muhammadiyah Gresik Hospital, covering menu planning, food preparation, cooking, storage, distribution, and patient meal service. This research employed a descriptive qualitative method. Data were collected through observations and in-depth interviews with the head of the nutrition installation, dietitians, food production staff, and food distribution officers. The data were analyzed through data reduction, data presentation, and conclusion drawing by comparing the findings with relevant theories and previous studies.The results showed that the implementation of the cook-fresh system at the Nutrition Installation of Muhammadiyah Gresik Hospital has been carried out in accordance with the applicable Standard Operating Procedures (SOPs). All stages of food production have applied hygiene, sanitation, and food safety principles. Temperature control during food production, the application of FIFO (First In, First Out) and FEFO (First Expired, First Out) methods in food storage, and timely food distribution contributed to maintaining the quality and safety of patient meals. However, improvements are still needed in the consistency of temperature recording and monitoring compliance with SOPs.